Two mini transverse-incision repair yields better results than percutaneous repair for acute closed midsubstance Achilles tendon rupture: a retrospective case-control study - Jin, Wen Tao; Huang, Li Fang; Guo, Hai Hua; Wang, Lei; Li, Xiang; Wang, Ze Jin (Journal of orthopaedic surgery and research, 2024)
Acute closed midsubstance Achilles tendon rupture(ACMATR) is common, with various treatment methods developed over time. We retrospectively compared the two mini transverse-incision repair (2MTIR) with percutaneous repair (PR) to determine which method yields better results. All cases meeting criteria from 2018 to 2021 in our hospital were included and followed up for 1 to 5 years. A final questionnaire with multiple indexes was conducted via phone call. Comparative analysis of these indexes between the two groups was performed using IBM SPSS Statistics (V.26). Continuous variables that passed tests for normality and equal variance were compared using the Student's t-test. Ranked data were compared using the Mann-Whitney U test. Categorical variables were tested with the chi-square test or Fisher's exact test. A p-value of less than 0.05 was considered statistically significant. There was one rerupture in the PR group. The final indexes for "Tightness Feeling", "Heel Rising Strength", and "Foot Numbness" were statistically different (P < 0.05) between the two groups. The "Re-rupture" and "Return to Sports" indexes showed no statistical difference (P > 0.05). The 2MTIR technique provided a technically straightforward, minimally invasive procedure with well-preserved paratenon and direct end-to-end firm fixation in cases of ACMATR. It resulted in very low complications, easy rehabilitation, and full weight-bearing as early as 5-6 weeks postoperatively, yielding better functional outcomes compared to the PR technique in the 1-5 year follow-up. The study was preliminarily registered and approved by the University of Hong Kong-Shenzhen Hospital Ethical Board with Project number: hkuszh2023074 on May 4, 2023.